2018
DOI: 10.1371/journal.pone.0204734
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and agreement of the CT appearance pattern and its severity grading of radiation-induced lung injury after stereotactic body radiotherapy for lung cancer

Abstract: PurposeRadiographic severity of radiation-induced lung injury (RILI) has not been well-studied. The goal of this study was to assess the CT appearance pattern and severity of RILI without consideration of the clinical presentation.Material and methodsA total of 49 patients, 41 with primary lung cancer and 8 with metastatic lung cancer, were treated by 4-fraction stereotactic body radiotherapy (SBRT). RILI after SBRT was separately assessed by two observers. The early and late CT appearance patterns and CT-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…The main novelty of this RGS was based on the hypothesis that higher numbers of lung segments affected by RILI reflect an increased inflammatory response to RT and thus could determine both the severity of RILI and the occurrence of RP. Previous scales used either general terms to describe RILI (Additional file 2: Table A.2) or the percentage of lung volume affected by RILI [25]. The latter is also empirically based, but is more challenging to quantitate from a radiological perspective.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The main novelty of this RGS was based on the hypothesis that higher numbers of lung segments affected by RILI reflect an increased inflammatory response to RT and thus could determine both the severity of RILI and the occurrence of RP. Previous scales used either general terms to describe RILI (Additional file 2: Table A.2) or the percentage of lung volume affected by RILI [25]. The latter is also empirically based, but is more challenging to quantitate from a radiological perspective.…”
Section: Discussionmentioning
confidence: 99%
“…There are few published reports of inter-observer variability regarding RILI and RP grading scales [25,27], but none regarding the prediction of RP. A study by Yamamoto et al [25] reported a 60% agreement between two observers (Kappa value 0.6).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations